Simulation studies to profile development and control of mixed-culture static and dynamic biofilms during extended raw beef processing operations using combinations of nanobubble water and peracetic acid - Abi Nakhoul, Yara (My University, 2025)
Biofilms are the dominant mode of bacterial growth in nature, known for their exceptional resilience and ability to withstand common cleaning and sanitizing procedures, thereby posing significant challenges for the food industry in maintaining safety and quality standards. Multiple studies have investigated technologies to eradicate and control biofilm development on hard surfaces, however, few have taken into consideration the effect of organic residue accumulation and natural microflora presence in simulated beef processing conditions—even though mixed-species biofilms remain the most common form encountered in real-world settings. This research evaluates the application of nanobubble water (NW)—recognized for its potential antimicrobial properties—in combination with peroxyacetic acid (PAA)—a strong oxidizer commonly used in meat processing—to control mixed-species biofilm development on stainless steel (S304) and rubber (Buna-N) surfaces over extended processing times. Experiments were conducted under simulated beef processing conditions at 4°C, using either tap water (TW) or NW combined with 0, 200 or 400 ppm of PAA. Solutions contained organic matter added in the form of beef purge and were replenished daily with 20% (v/v) new solution and purge. Two important meat industry scenarios were simulated: static biofilm development (Chapter 3) and dynamic biofilm development using the Centers for Disease and Control (CDC) biofilm reactor (Chapter 4). Both planktonic (free in solution) and attached bacterial cells (biofilm on coupons) were assessed for Aerobic Plate Count (APC) and Enterobacteriaceae (EB) populations. Treatment solutions were inoculated with a cocktail of five USDA-approved non-pathogenic Escherichia coli strains (surrogates for pathogenic Shiga toxin-producing E. coli), while control samples remained non-inoculated. The static study tested the efficacy of antimicrobial solutions with 5% or 10% (v/v) beef purge over an extended period of 10 days. Results showed that organic matter content significantly affected biofilm development in 200 ppm PAA solutions (P < 0.0001), reaching 4.5 log APC/coupon at 10% purge compared to 2.0 logs at 5% purge. At 400 ppm PAA, APC biofilm development was higher (P = 0.043) in TW solutions, but similar (P = 0.16) in NW solutions between organic levels. There was no difference (P>0.05) between using TW or NW in the treatment solutions against planktonic cells or biofilm control in the static setting. The dynamic study tested treatment solutions at the 10% beef purge level over a 5-day period. Results showed that 200 ppm PAA, regardless of water type, inhibited EB biofilm formation but allowed approximately 2.5 log CFU/coupon of native mixed-culture biofilm (represented by APC Petrifilm counts) to develop on both coupon materials. 400 ppm PAA solutions completely inhibited both APC and EB biofilm growth on coupons. The use of NW alone (no PAA added) resulted in a 0.7 log reduction of APC biofilm after 5 days compared to TW alone, demonstrating its slight effect against biofilm development (P = 0.0269). In general, PAA at [greater than or equal to] 200 ppm inhibited biofilm development by native meat microflora on S and R surfaces under both static and dynamic, extended duration, refrigerated conditions encountered in meat processing, with a strong influence by the level of organic loading present. This finding serves to support the continued use of PAA which is commonly applied in beef manufacturing operations but suggests that additional biofilm control can be realized if the PAA is applied in NW versus typical municipal TW.
Keywords: Meat safety; Biofilms; Sanitation; Peracetic acid; Food microbiology